2015
DOI: 10.1097/tp.0000000000000781
|View full text |Cite
|
Sign up to set email alerts
|

Early Postoperative Emergency Department Care of Abdominal Transplant Recipients

Abstract: Background Research on post-transplant care has predominantly focused on predictors of readmission with little attention to emergency department (ED) visits. The goal of this study was to describe early postoperative ED care of transplant recipients. Methods A secondary database analysis of adult patients who underwent abdominal organ transplantation between January 1, 2008 and December 31, 2013 and sought ED care within one year post-transplantation was conducted. Survival was compared using the Kaplan-Meie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
(27 reference statements)
1
16
0
Order By: Relevance
“…Transplant recipient requiring ED referral has been recently investigated and seems to be common . Within the first year after transplantation, 60%, 53.2%, 44.4%, and 32.6% of pancreas transplant, multiorgan transplant, liver transplant, and kidney transplant recipients sought care in ED, respectively . Also, the majority of ED referral in transplant recipients were made by renal patients (66.2%) followed by liver (24.5%) and combined renal (9.3%) transplant recipients .…”
Section: Prevalence and Incidence Of Lt Recipient In Emergency Departmentioning
confidence: 99%
See 2 more Smart Citations
“…Transplant recipient requiring ED referral has been recently investigated and seems to be common . Within the first year after transplantation, 60%, 53.2%, 44.4%, and 32.6% of pancreas transplant, multiorgan transplant, liver transplant, and kidney transplant recipients sought care in ED, respectively . Also, the majority of ED referral in transplant recipients were made by renal patients (66.2%) followed by liver (24.5%) and combined renal (9.3%) transplant recipients .…”
Section: Prevalence and Incidence Of Lt Recipient In Emergency Departmentioning
confidence: 99%
“…Also, the majority of ED referral in transplant recipients were made by renal patients (66.2%) followed by liver (24.5%) and combined renal (9.3%) transplant recipients . Finally, in a 5‐year report, a total of 37.4% unique recipients sought ED care …”
Section: Prevalence and Incidence Of Lt Recipient In Emergency Departmentioning
confidence: 99%
See 1 more Smart Citation
“…The 48% risk of an ED visit leading to a hospital admission in this sample compares with an overall national risk of 11%, suggesting that the higher ED visit rate among post-transplant patients may be driven largely by medical need rather than overuse of the ED. Other studies have also found high risks of admission among kidney transplant recipients who seek ED care (4,5). One interpretation of these findings is that there may be a low threshold to admit transplant recipients to the hospital; these admission decisions may differ between transplant centers and community hospitals.…”
mentioning
confidence: 99%
“…Over the past 15 years, ED utilization has grown from 36.5 to 42.8 visits per 100 person-years, despite a decline in the total number of ED facilities (3). However, few studies have examined ED utilization after kidney transplantation, and the published studies have been limited to transplant recipients at a single center (4,5). In 2013 in the United States, 17,600 kidney transplantations were performed, and .190,000 people were living with a functioning kidney transplant (6), highlighting the importance of understanding care utilization in this high-risk population.…”
mentioning
confidence: 99%